Imposed thermal gradients and resultant residual stresses: physical and numerical simulations. Issue 10 (2nd July 2020) - Mukherjee, D.; Tewary, U.; Kumar, S.; Karagadde, S.; Verma, R. K.; Sambandam, M.; Samajdar, I.
ABSTRACT: In this study, physical simulations were carried out on High Strength Low Alloy (HSLA) steel specimens. Samples were heated above and below the austenite transformation temperature and then cooled at different rates. Thermal history and residual stress gradients were measured experimentally and simulated numerically. This involved finite element simulations, which solved the Fourier's heat conduction equation and also incorporated appropriate subroutines for phase transformations. The latter involved HETVAL, to quantify phase transformation, and USDFLD, to calculate the corresponding heat inputs. This manuscript not only established a similar pattern between the controlled experiments and the numerical simulations but also provided a quantitative perspective to residual stress gradients, as introduced by temperature gradients and by phase transformations, during thermomechanical processing.